Feasibility Study of Implementing Solar Photovoltaic Systems under Net Energy Metering Scheme in UTeM - Kim Gan, Chin; Salah Mohammed, Hayder; Azmi Baharin, Kyairul; Ruddin Ab Ghani, Mohd; Nazri Othman, Md (International Journal of Engineering and Technology, 2018)
The Malaysian government has introduced the Net Energy Metering (NEM) programme in November 2016 as one of the measures to encourage the development of renewable energy in Malaysia. In light of this, this paper aims to investigate the feasibility of installing solar photovoltaic system in UTeM under this NEM scheme. To achieve this, historical solar irradiation profiles were obtained from the commercially available database. This is to estimate the expected solar output generation. This is important as the amount of solar generation will ultimately translate into the revenue that is needed to justify the investment decision. As a state funded university, UTeM is enjoying a special subsided electricity tariff rate. Hence, the analyses have suggested that the rate of return of such an initiative is relatively low and unattractive for the investor in the economic point of view. Â Â